Structure–Activity and Structure–Toxicity Relationships of Peptoid‐Based Histone Deacetylase Inhibitors with Dual‐Stage Antiplasmodial Activity. (19th February 2019) - Mackwitz, Marcel K. W.; Hesping, Eva; Antonova‐Koch, Yevgeniya; Diedrich, Daniela; Woldearegai, Tamirat Gebru; Skinner‐Adams, Tina; Clarke, Mary; Schöler, Andrea; Limbach, Laura; Kurz, Thomas; Winzeler, Elizabeth A.; Held, Jana; et al.
Abstract: Novel malaria intervention strategies are of great importance, given the development of drug resistance in malaria‐endemic countries. In this regard, histone deacetylases (HDACs) have emerged as new and promising malaria drug targets. In this work, we present the design, synthesis, and biological evaluation of 20 novel HDAC inhibitors with antiplasmodial activity. Based on a previously discovered peptoid‐based hit compound, we modified all regions of the peptoid scaffold by using a one‐pot multicomponent pathway and submonomer routes to gain a deeper understanding of the structure–activity and structure–toxicity relationships. Most compounds displayed potent activity against asexual blood‐stage P. falciparum parasites, with IC50 values in the range of 0.0052–0.25 μm and promising selectivity over mammalian cells (SI Pf 3D7/HepG2 : 170–1483). In addition, several compounds showed encouraging sub‐micromolar activity against P. berghei exo‐erythrocytic forms ( Pb EEF). Our study led to the discovery of the hit compound N ‐(2‐(benzylamino)‐2‐oxoethyl)‐ N ‐(4‐(hydroxycarbamoyl)benzyl)‐4‐isopropylbenzamide (2 h ) as a potent and parasite‐specific dual‐stage antiplasmodial HDAC inhibitor (IC50   Pf 3D7=0.0052 μm, IC50   Pb EEF=0.016 μm ). Abstract : Dual‐stage power : The synthesis and biological evaluation of a series of novel peptoid‐based HDAC inhibitors (HDACi) is presented. All compounds were screened for activity against three different malaria parasite life‐cycle stages as well as for mammalian cell toxicity to investigate the structure–activity and structure–toxicity relationships of this class of antiplasmodial HDACi. Compound2 h was identified as a parasite‐selective HDACi with potent dual‐stage antiplasmodial activity.